2014
DOI: 10.1001/jama.2014.5988
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bariatric Surgery With Long-term Remission of Type 2 Diabetes and With Microvascular and Macrovascular Complications

Abstract: In this very long-term follow-up observational study of obese patients with type 2 diabetes, bariatric surgery was associated with more frequent diabetes remission and fewer complications than usual care. These findings require confirmation in randomized trials. TRIAL REGISTRATION clinicaltrials.gov Identifier: NCT01479452.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
645
2
28

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 896 publications
(705 citation statements)
references
References 40 publications
30
645
2
28
Order By: Relevance
“…Furthermore, we recently showed that diabetes remission is markedly higher in operated patients [9]. We now extend these findings and show that for a given degree of weight loss, from a minor weight reduction (1-9 BMI units) to a major weight reduction (over 15 BMI units), the effect of surgery on diabetes prevention and remission was independent of the initial BMI level.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Furthermore, we recently showed that diabetes remission is markedly higher in operated patients [9]. We now extend these findings and show that for a given degree of weight loss, from a minor weight reduction (1-9 BMI units) to a major weight reduction (over 15 BMI units), the effect of surgery on diabetes prevention and remission was independent of the initial BMI level.…”
Section: Discussionsupporting
confidence: 72%
“…Type 2 diabetes was defined as fasting blood glucose of 6.1 mmol/l or higher, corresponding to a fasting plasma glucose of 7.0 mmol/l or higher, or diabetes medication use (insulin, oral glucose-lowering drugs, or both). Diabetes remission was defined as blood glucose levels lower than 6.1 mmol/l and no diabetes medication [3,9].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…in 1995 82. Strong evidence has shown that bariatric surgery is an effective treatment for severe obesity (BMI >35 kg/m 2 ) and results in marked improvement of T2DM control 10, 83, 84. Derived from bariatric surgery, metabolic surgery is focused on T2DM treatment in mildly obese or overweight patients (BMI <35 kg/m 2 ) 85.…”
Section: From Bariatric To Metabolic Surgerymentioning
confidence: 99%